Rationalization of the X-ray photoelectron spectroscopy of aluminium phosphates synthesized from different precursors. Issue 14 (26th February 2020) - Bemmer, Victoria; Bowker, Michael; Carter, James H.; Davies, Philip R.; Edwards, Lee E.; Harris, Kenneth D. M.; Hughes, Colan E.; Robinson, Fiona; Morgan, David J.; Thomas, Matthew G.
Abstract : Using NMR, XRD and FTIR we clarify the assignment of XP spectra of aluminium phosphates prepared from three different aluminium precursors [Al(OH)3, Al(NO3 )3 and AlCl3 ] at different annealing temperatures. Abstract : The aim of this paper is to clarify the assignments of X-ray photoelectron spectra of aluminium phosphate materials prepared from the reaction of phosphoric acid with three different aluminium precursors [Al(OH)3, Al(NO3 )3 and AlCl3 ] at different annealing temperatures. The materials prepared have been studied by X-ray photoelectron spectroscopy (XPS), powder X-ray diffraction (XRD), infrared spectroscopy and high-resolution solid-state 31 P NMR spectroscopy. A progressive polymerization from orthophosphate to metaphosphates is observed by XRD, ATR-FTIR and solid state 31 P NMR, and on this basis the oxygen states observed in the XP spectra at 532.3 eV and 533.7 eV are assigned to P–O–Al and P–O–P environments, respectively. The presence of cyclic polyphosphates at the surface of the samples is also evident.